Remembering Marielle Franco from a Theological Perspective A Teaching in Individual and Collective Self-Empowerment - Merian, Katharina; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
In this Open Access book, Katharina Merian discusses memories of Marielle Franco from the perspective of the concept of dangerous memory introduced by the political theologian Johann Baptist Metz. Franco was an Afro-Brazilian human-rights activist and city councilor of Rio de Janeiro who was assassinated on March 14, 2018. Her murder elicited worldwide protest and empathy. Today she is considered an international symbol in the fight for human, women, and LGBTQ+ rights. Based on the memories of people from Franco$1 (Bs inner circle, the study explores Franco$1 (Bs life, what it meant to the people around her, and how her image was transformed following her murder. By critically engaging with Metz$1 (Bs concept of dangerous memory, which concerns memories of suffering and unfulfilled hopes that challenge the present, Merian demonstrates that the memories of Franco represent a decolonial dangerous memory that sparks individual and collective self-empowerment among Black women, members of the LGBTQ+ community, and favela residents. This work not only contributes to a critical reappraisal of Franco$1 (Bs story and the meaning of her memory in the Brazilian and international context but also proposes a differentiated understanding of dangerous memory that highlights the relationship between solidarity and self-empowerment in a moment of existential danger and threat. Katharina Merian is a senior research associate at the Faculty of Theology and Study of Religion of the University of Zurich in Switzerland.s
Chapter1: Introduction -- Chapter2: Dangerous Memory in Johann Baptist Metz$1 (Bs Political Theology -- Chapter3: Interview Analysis: Remembering Marielle Franco -- Chapter4: Discussion: Toward a Decolonial Dangerous Memory of Individual and Collective Self-Empowerment -- Chapter5: Concluding Remarks.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Theology; Liberation theology; America -- History; Political science; Christian Theology; Liberation Theology; History of the Americas; Political Theory